Potentials of Charcoal Productions from Community Forest in Bangunjiwo Village, Kasihan Sub Regency, Bantul, Yogyakarta - Ris Hadi Purwanto; Nius Abdi Ginting (Jurnal Ilmu Kehutanan)
Asam jawa (Tamarindus indica) and mahoni (Swietenia macrophylla) which predominantly grow on the community forests of Bangunjiwo Village are an ideal candidate as raw matterial of charchoal production because they're hard wood makes good quality charchoal and income from its charchoal are an attractive source of supplemental revenue. Information on its charchoal production are needed, but this information is currently lacking. The potential of charcoal production of woody perennial in the community forests were estimated by developing allometric equations for standing trees. To establish the equations 30 sample logs of tamarind and 29 sample logs of mahoni were made charcoal by traditional kiln to determine the relationships between the mechantable timber volume/log (Vkp) and its charcoal production (Pa). The raw material of charcoal production from the merchantable timber volume in the community forests was the ligneous material contained in the bole and branches which both with a diameter of at least 7 cm. The results showed that the merchantable timber volume was strongly related to the charcoal production (tamarind: Pa = 185.6180 (Vkp)0.9455, n = 30, r2  = 0.9559; mahoni: 321.2263 (Vkp)1.0725, n = 29, r2  = 0.9459; mixed: = 235.0601 (Vkp)1.0008, n = 59, r2  = 0.9465). The potential of charcoal production in the community forests was then estimated based on the allometric equations. The potential of charcoal production in these community forests was 12.067 ton/ha, equal to Rp  21.117.250,00 /ha which contributing the forest to the regional income.